1988
DOI: 10.1111/j.1432-1033.1988.tb14297.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inducible polyamine transporter in bovine lymphocytes

Abstract: The polyamine uptake system in bovine lymphocytes was activated by concanavalin A. The system was common to putrescine, spermidine and spermine. The K, values for uptake activities of putrescine, spermidine and spermine were 3.7 pM, 0.38 pM and 0.23 pM in that order. The uptake activity was inhibited by carbonyl cyanide m-chlorophenylhydrazone, gramicidin D or valinomycin in the presence of 20 mM IS+ suggesting that polyamine uptake depends on the membrane potential. The uptake activity appeared 10 h after add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 23 publications
11
55
0
Order By: Relevance
“…The results illustrate how polyamine catabolism as regulated by SSAT and polyamine biosynthesis as regulated by ODC can be rapidly and simultaneously controlled by intracellular pools. These responses, together with that of polyamine transport which is also known to be regulated by polyamines [7][8][9], function in a coordinated manner to sensitively maintain intracellular polyamine pools at a relatively constant level [3]. Such a homeostatic system would ensure an adequate supply of polyamines for cell growth while at the same time preventing cellular toxicity due to polyamine excess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results illustrate how polyamine catabolism as regulated by SSAT and polyamine biosynthesis as regulated by ODC can be rapidly and simultaneously controlled by intracellular pools. These responses, together with that of polyamine transport which is also known to be regulated by polyamines [7][8][9], function in a coordinated manner to sensitively maintain intracellular polyamine pools at a relatively constant level [3]. Such a homeostatic system would ensure an adequate supply of polyamines for cell growth while at the same time preventing cellular toxicity due to polyamine excess.…”
Section: Discussionmentioning
confidence: 99%
“…These effectors are short-lived and differentially regulated by intracellular polyamine pools [3]. Exposure to exogenous polyamines causes polyamine biosynthesis (reviewed in [5,6]) and uptake [7][8][9] to decrease and polyamine catabolism to increase *Corresponding author. Fax: (1) (716) 845-8857.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that, under basal conditions, steady-state levels of SSAT expression are probably maintained in a partially up-regulated state by basal polyamine pools since a decline in these pools results in a decrease in SSAT activity and mRNA. Polyamine transport and the polyamine biosynthetic enzymes, ODC and SAMDC, seem to be similarly maintained under basal conditions but via an inverse relationship since a decline in pools causes an increase in their expression [1,26] and vice versa [ 1,2].…”
Section: Discussionmentioning
confidence: 99%
“…The former was apparent from experiments with exogenous polyamines and the latter by pool depletion with specific enzyme inhibitors. The biosynthetic enzymes, ODC and SAMDC [l], and the polyamine transport system [2,31,32,35], are also sensitively upregulated and down-regulated by changes in intracellular polyamine pools. Unlike SSAT, however, the regulatory relationships for these systems are negative in nature -as pools decrease, enzyme and transport activities increase and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have shown that cells fed with spermidine or spermine will rapidly incorporate these until intracellular polyamine levels are slightly above normal (1-2 h), at which time uptake is abruptly terminated [14][15][16][17]. We [18] and others [19] have demonstrated that such attenuation of polyamine uptake could be prevented by the simultaneous inhibition of protein synthesis with cycloheximide.…”
Section: Introductionmentioning
confidence: 99%